Raman spectroscopy of graphene under ultrafast laser excitation - C. Ferrante (Nature Portfolio, 2018)
Non-equilibrium ultrafast processes in graphene entail relaxation pathways involving electron–electron and electron–phonon scattering events. Here, the authors probe graphene optical phonons at high electronic temperatures by means of Raman spectroscopy under pulsed excitation